A clinicopathological case of retinopathy of prematurity (ROP) treated by peripheral cryopexy. Issue 1 (January 1984) - Nissenkorn, I; Kremer, I; Ben Sira, I; Cohen, S; Garner, A
Abstract : A baby born at 25 weeks gestation with a birth weight of 800 g who suffered from severe respiratory distress syndrome with metabolic acidosis is described. Active retinopathy of prematurity, stages II and III, was found in the right eye at the age of 1 month and in the left eye a month later. Both eyes were treated by peripheral cryopexy. The pathological examination showed that cryopexy was effective in preventing progression of the retinopathy to cause severe cicatrisation.